The modern Assyrians of the Middle East : encounters with Western Christian missions, archaeologists, and colonial powers - Joseph, John, 1923- (Studies in Christian Mission, 2000)
This is a revised edition of the author's The Nestorians and Their Muslim Neighbors (Princeton University Press, 1961). Early in the nineteenth century, the Aramaic-speaking \'Nestorian\' Christians received special attention when American Protestant missions decided to educate and reform them to help meet the challenge that Islam presented to the growing missionary movements. When archaeologist Layard further publicized the historic minority as \'Assyrians\', the name acquired a new connotation when other forces at work in the region - religious, nationalistic, imperialistic - entangled these modern Assyrians in vagaries and manipulations in which they were outnumbered and outclassed. The study examines Western Christendom's current position on Islam, with emphasis on the Roman Catholic Church and the World Council of Churches. The revision draws on a wide variety of sources not used in the original.